La psicomotricidad fina y el inicio de la pre escritura en los niños y niñas de 4-5 años de la Escuela General de Educación Básica Reino de Bélgica del Cantón Guano, Provincia de Chimborazo Año Lectivo 2013 – 2014 - Martínez Silva, Nancy del Pilar (2016)
Prior to a diagnosis of identified problems, priority is given to one of the primary difficulties in which the children of the fifth year of basic education of the Garcia Moreno school of the sector the Batán of the canton of Riobamba, province of Chimborazo, hence comes the importance and need for an in- depth study concerning "The dysorthography in the low performance of the area of Language and Literature", making reference that this docs not become a difficulty in learning by preventing the learner the normal development in empowering their cognitive, affective and motive capacities, serving as the foundation the frame of reference where it arises and the problem is formulated where objectives are set and the justification of the theoretical framework outlines the scientific foundations as a core part of the study for theoretical foundation has been taking into account the development of the two variables, within the methodological framework the design and type of research is referred, working with 22 subjects that make up the entire population, as a technic and methods the observation is applied and as an instrument tab collations the same that allowed us to analyze and interpret 'the results proving the hypothesis the respective conclusions and recommendations are issued the same as determined necessary to design a guidance manual "Reconociendo Letritas" to improve the problem and thus help in the process of inter learning of an active and creative way with activities easy to apply where it was possible that the child is visually discriminating forms and commands of each letter to identify their writing, recognize patterns and sequences and to improve in this way the dysorthography problems, for teachers to achieve a meaningful and functional learning.